Neuromuscular and Cardiovascular Adaptations During Concurrent Strength and Endurance Training in Untrained Men - Mikkola, J.; Rusko, H.; Izquierdo, M.; Gorostiaga, E. M.; Häkkinen, K. (International Journal of Sports Medicine, 2012)
This study examined the effects of concurrent strength and endurance training on neuromuscular and endurance characteristics compared to strength or endurance training alone. Previously untrained men were divided into strength (S: n=16), endurance (E: n=11) or concurrent strength and endurance (SE: n=11) training groups. S and E trained 2 times and SE 2 + 2 times a week for strength and endurance during the 21-week period. Maximal unilateral isometric and bilateral concentric forces of leg muscles increased similarly in S and SE by 20–28% (p<0.01) and improvements in isometric forces were accompanied by increases (p<0.05) of maximal muscle activation. Rate of force development of isometric action (p<0.05) improved only in S. The increase in muscle cross-sectional area of the quadriceps femoris in SE (11%, p<0.001) were greater than in S (6%, p<0.001) or in E (2%, p<0.05). SE and E increased maximal cycling power (SE: 17% and E: 11%, p<0.001) and VO2MAX (SE: 17%, p<0.001 and E: 5%, ns.). These results suggest that the present moderate volume 21-week concurrent SE training in previously untrained men optimizes the magnitude of muscle hypertrophy, maximal strength and endurance development, but interferes explosive strength development, compared with strength or endurance training alone.
Keywords: maximal strength; resistance training; endurance performance; rate of force development; muscle hypertrophy